Recent advances in the diagnosis and management of glaucoma. Issue 1 (January 2015) - Azarbod, Parham; Crawley, Laura; Ahmed, Faisal; Cordeiro, M Francesca; Bloom, Philip
<x xml:space="preserve">Abstract</x> Reducing intraocular pressure remains the only treatment option in glaucoma, however, prompt evaluation and management can prevent blindness and a lifetime of disability. Our Drug Review outlines the key points and recent advances in diagnosis and management.